Without Remorse - Clancy, Tom (London HarperCollins Publishers, 1998)
Tom Clancy takes us back to a formative episode in the life of John Kelly, a character familiar to his many readers as CIA legend Mr Clark, in his seventh No 1 bestselling thriller - now reissued with a new cover.
English Fiction.
Keywords: Clark, John (Fictitious character) -- Prisoners of war -- Vietnam